Elizabeth von Arnim's The Pastor's Wife: A Reassessment. Issue 1 (3rd April 2017) - Turner, Nick
Abstract: The Pastor's Wife (1914) may seem at first reading simply another depiction of a woman struggling for liberation in the decades following the work of Thomas Hardy and Henrik Ibsen, being the story of how Ingeborg Bullivant escapes from an English patriarchal home, only to find herself trapped in another one in Germany. The novel, however, marks a turning point in Elizabeth von Arnim's career; it is a novel that looks back to previous themes while anticipating those to come. It demonstrates, with comedy and bitterness, themes of alienation and exile; satirizes German codes and class; and provides a lyrical Romantic vision of the natural world. It also presents the married woman as a prisoner in a way that anticipates Vera (1921). The novel can also stand alone as an underrated classic that plays an important part in the history of English literature. Published at the beginning of high modernism, it shows, unlike the work of some canonized writers of the time, a fusion of realism and modernism. This essay argues that the novel is a proto-feminist work that is radical in its portrayal of women's experience and influenced by literary naturalism in its childbirth scenes, but pessimistic about possibilities for change. The essay shows how the novel is modernist in its depiction of the alienated experience of the city; uses nineteenth-century realism in its narrative structure and comedy; and yet is forward-looking in its use of endings. A book that begins as a comedy but ends as a tragedy, The Pastor's Wife deserves equal recognition with the work of H. G. Wells and E. M. Forster, writers with whom von Arnim was connected and by whom she was influenced.